Causal association of gut microbiota and esophageal cancer: a Mendelian randomization study - Gao, Xiangyu; Wang, Zhiguo; Liu, Bowen; Cheng, Yufeng (Frontiers in Microbiology, 2023)
Despite the growing body of evidence, the link between the gut microbiota and different types of tumors, such as colorectal, gastric, and liver cancer, is becoming more apparent. The gut microbiota can be used as a reference for evaluating various diseases, including cancer, and can also act as risk factors or preventive factors. However, the specific connection between the gut microbiota and the advancement of esophageal cancer has yet to be investigated. Therefore, the aim of this research is to clarify the possible causal influence of intestinal microorganisms on the vulnerability to esophageal cancer through the utilization of Mendelian randomization (MR) studies. In this study, we employed a two-sample Mendelian randomization approach to evaluate the unbiased causal association between 150 different gut microbiota types and the occurrence of esophageal cancer. Following the selection from the IEU GWAS database and SNP filtration, we utilized various MR statistical techniques on the suitable instrumental variables. These included IVW methods, employing inverse variance weighting. Additionally, we performed a range of sensitivity analyses to confirm the heterogeneity and pleiotropy of the instrumental variables, thus ensuring the reliability of the outcomes. The increased likelihood of developing esophageal cancer is linked to the genetically predicted high levels of Gordonibacter, Oxalobacter, Coprobacter, Veillonella, Ruminiclostridium 5, Ruminococcus 1, and Senegalimasilia genera. Conversely, a decreased risk of esophageal cancer is associated with the high abundance of Turicibacter, Eubacterium oxidoreducens group, Romboutsia, and Prevotella 9 genera. No heterogeneity and pleiotropy were detected in the sensitivity analysis. We found that 11 types of gut microbial communities are associated with esophageal cancer, thereby confirming that the gut microbiota plays a significant role in the path.